2011
DOI: 10.1159/000329727
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Marine Omega-3 Fatty Acids on Serum Systemic and Vascular Inflammation Markers and Oxidative Stress in Hemodialysis Patients

Abstract: Background and Aims: High concentrations of serum inflammation markers, especially vascular inflammation markers, are an important risk factor for cardiovascular diseases in hemodialysis patients. The present study was designed to investigate the effects of marine omega-3 fatty acids on serum systemic and vascular inflammation markers and oxidative stress in hemodialysis patients. Methods: Thirty-four hemodialysis patients were randomly assigned to either the marine omega-3 fatty acid or the placebo group. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 59 publications
0
23
0
1
Order By: Relevance
“…48 studies including 61 independent comparisons involved patients with chronic non-autoimmune disease as subjects [19][21], [35]–[39], [42][44], [46][48], [50], [52], [53], [56], [58][63], [65], [67], [68], [70][78], [80], [83], [84], [86], [88], [89], [92], [94][98], 2 studies including 2 independent comparisons involved patients with chronic auto-immune disease as subjects [57], [93], and 17 studies including 22 independent comparisons involved healthy people as subjects [22], [40], [41], [49], [51], [54], [55], [64], [66], [69], [79], [81], [82], [85], [87], [90], [91]. In addition, one study including one independent comparison recruited both subjects with chronic non-autoimmune disease and subjects with chronic autoimmune disease [45].…”
Section: Resultsmentioning
confidence: 99%
“…48 studies including 61 independent comparisons involved patients with chronic non-autoimmune disease as subjects [19][21], [35]–[39], [42][44], [46][48], [50], [52], [53], [56], [58][63], [65], [67], [68], [70][78], [80], [83], [84], [86], [88], [89], [92], [94][98], 2 studies including 2 independent comparisons involved patients with chronic auto-immune disease as subjects [57], [93], and 17 studies including 22 independent comparisons involved healthy people as subjects [22], [40], [41], [49], [51], [54], [55], [64], [66], [69], [79], [81], [82], [85], [87], [90], [91]. In addition, one study including one independent comparison recruited both subjects with chronic non-autoimmune disease and subjects with chronic autoimmune disease [45].…”
Section: Resultsmentioning
confidence: 99%
“…Another factor that could potentially explain the contradictory finding in our study with those studies is baseline levels of inflammatory markers. Omega-3 supplementation appears to be more effective in studies reporting higher baseline CRP (>13.8 mg/dL) than those that did not 17,38,44…”
Section: Discussionmentioning
confidence: 96%
“…Saifullah et al showed that a supplementation of 1.3 g of oral EPA and DHA daily over a period of 3 months could modestly reduce CRP levels 37. However, a recent study using a larger dosage (2.08 g/day) but a shorter duration (10 weeks) showed no effects on serum systemic inflammatory markers (CRP, interleukin-6, tumor necrosis factor-α) and oxidative stress (malondialdehyde, total antioxidant capacity) 38. In a prospective cohort study by Noori et al, the authors showed that a lower omega-6 to omega-3 ratio (~6) was associated with decreased inflammation and overall mortality in hemodialysis patients which indicates the importance of n-6/3 polyunsaturated fatty acid ratios in the diet 13.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrate that marine omega-3 supplementation did not change significantly oxidative stress parameters in HD patients. [21]…”
Section: Discussionmentioning
confidence: 99%